Tourism potential of Lake Tudakul in Navoi region - Shakhrizoda, Kholmirzaeva; Sadriddinovna, Amriddinova Rayhona (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
This article describes the possibilities for the development of water tourism at the Tudakul Lake, located in the Kyzyltepa district of the Navoi region republic of Uzbekistan